Brand Image Memediasi Antara Celebrity Endorser Terhadap Keputusan Pembelian - Krental Lady Day Surbakti; Dewi Nuraini (STIMI Handayani Denpasar, 2023)
This study aims to find out how the influence of brand image mediates between celebrity endorsements and purchasing decisions (based on studies on skintific products at Tiktokshop). Tiktok shop customers who buy Skintific skincare are the population of this study. In this study, 120 respondents were used as a sample, and 100 respondents were returned. The sampling method involves using a questionnaire and distributing it through the Google form. In this study, the SPSS program was used to perform multiple regression analysis as well as the Sobel test using the website. Based on the findings of this study, the celebrity endorser variable has a significant effect on brand image; brand image has a significant impact on purchasing decisions; the celebrity endorser has a significant impact on the decision; and celebrity endorsers have a significant impact on brand image through purchasing decisions.